The Response Regulator RcsB Activates Expression of Mat Fimbriae in Meningitic Escherichia coli - Lehti, Timo A. (American Society for Microbiology, 2012)
The common colonization factor of Escherichia coli, the Mat (also termed ECP) fimbria, functions to advance biofilm formation on inert surfaces as well as bacterial adherence to epithelial cells and subsequent colonization. We used global mini-Tn5 transposon mutagenesis to identify novel regulators of biofilm formation by the meningitic E. coli isolate IHE 3034. Of the 4,418 transformants, we found 17 that were impaired in biofilm formation. Most of these mutants were affected in lipopolysaccharide synthesis and were reduced in growth but not in Mat fimbria expression. In contrast, two mutants grew well but did not express Mat fimbria. The insertions in these two mutants were located at different sites of the rcsB gene, which encodes a DNA-binding response regulator of the Rcs response regulon. The mutations abrogated temperature-dependent biofilm formation by IHE 3034, and the phenotype correlated with loss of mat expression. The defect in biofilm formation in the rcsB mutant was reversed upon complementation with rcsB as well as by overexpression of structural mat genes but not by overexpression of the fimbria-specific activator gene matA. Monitoring of the mat operon promoter activity with chromosomal reporter fusions showed that the RcsB protein and an RcsAB box in the mat regulatory region, but not RcsC, RcsD, AckA, and Pta, are essential for initiation of mat transcription. Gel retardation assays showed that RcsB specifically binds to the mat promoter DNA, which enables its function in promoting biofilm formation by E. coli.